NCMP-25. CLINICAL FEATURES, NEUROLOGIC RECOVERY, AND RISK PREDICTION OF POST-OPERATIVE POSTERIOR FOSSA SYNDROME: A PROSPECTIVE STUDY. (9th November 2020) - Khan, Raja B; Patay, Zoltan; Kilmo, Paul; Huang, Jie; Onar-Thomas, Arzu; Kumar, Rahul; Boop, Frederick A; Raches, Darcy; Conklin, Heather; Sharma, Richa; Simmons, Andrea; Sadighi, Zsila; et al.
Abstract: INTRODUCTION: Posterior fossa syndrome (PFS) is a known consequence of medulloblastoma resection. Our aim was to clinically define PFS, its evolution over time, and ascertain risk factors for its development and poor recovery. METHODS: Children with medulloblastoma treated at St Jude Children's Research Hospital from 6/2013-7/2019 received standardized neurological examinations, before and periodically after radiation therapy. Most (98.3%) were enrolled on the ongoing multi-institutional protocol (SJMB12; NCT 01878617). RESULTS: Sixty (34%) of 178 evaluated children had PFS. Forty (23%) had complete mutism (PFS1) and 20 (11%) had diminished speech (PFS2). All children with PFS had severe ataxia and 42.5% of PFS1 had movement disorders. By multivariable analysis, younger age (p=0.0005) and surgery in a low-volume surgery center (p=0.0146) increased PFS risk, while SHH tumors had reduced risk (p=0.0025). Speech and gait returned in PFS1/PFS2 children at a median of 2.3/0.7 and 2.1/1.5 months respectively, however, 12 (44.4%) of 27 PFS1 children with 12 months of follow-up were non-ambulatory at one-year. Movement disorder (p= 0.037) and high ataxia score (p< 0.0001) were associated with delayed speech recovery. Older age (p= 0.0147) and high ataxia score (p< 0.0001) were association with delayed gait return. Symptoms improved in all children but no child with PFS had normal neurologic examination at a median of 23 months after surgery. CONCLUSION: Categorizing PFS in to types 1 and 2 has prognostic relevance. Almost half of the children with PFS1 remained non-ambulatory at 12-month follow-up. Surgical experience was a major modifiable contributor to the development of PFS.